2020
DOI: 10.3390/v12101119
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Human Papillomaviruses in the Nasopharynx of Breastfed Infants: New Findings and Meta-Analysis

Abstract: Vertical transmission of human papillomaviruses (HPVs) from mother to infant is known to occur during labor, delivery or breastfeeding. Infection with mucosal HPV 6 and 11 may cause recurrent respiratory papillomatosis in children, which is a rare and severe respiratory disease. The cutaneous HPV genotypes have also been described to be transmitted from mother to newborn through skin-to-skin contacts and during breastfeeding. To investigate the perinatal transmission of alpha and beta HPVs we collected nasopha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…The transmission of cutaneous HPV genotypes from a mother to her newborn is thought to occur through skin-to-skin contact and during breastfeeding. Recently, Dassi et al (2020) collected nasopharyngeal specimens from 0–12-month-old infants born by vaginal delivery (and breastfed at the time of sample collection) to investigate the perinatal transmission of α- and β-HPVs [ 121 ]. In total, 14 out of 113 (12.4%) samples tested positive for HPV and sequence analysis identified 8 β-genotypes (HPV 5b, 20, 25, 100, 107, 124, 152, and RTRX7).…”
Section: Hpv Can Be Acquired At Early Agementioning
confidence: 99%
See 1 more Smart Citation
“…The transmission of cutaneous HPV genotypes from a mother to her newborn is thought to occur through skin-to-skin contact and during breastfeeding. Recently, Dassi et al (2020) collected nasopharyngeal specimens from 0–12-month-old infants born by vaginal delivery (and breastfed at the time of sample collection) to investigate the perinatal transmission of α- and β-HPVs [ 121 ]. In total, 14 out of 113 (12.4%) samples tested positive for HPV and sequence analysis identified 8 β-genotypes (HPV 5b, 20, 25, 100, 107, 124, 152, and RTRX7).…”
Section: Hpv Can Be Acquired At Early Agementioning
confidence: 99%
“…However, though not widely studied yet, HPV-genotypes belonging to either β-, or γ-genera have been detected in sinonasal-, oral- and pharyngeal SCPs. [ 121 ]. More studies are clearly warranted to explore the role of β- and γ-HPV infections in the upper-aero-digestive tract, particularly in early childhood.…”
Section: Hpv Can Be Acquired At Early Agementioning
confidence: 99%
“…The most common transmission routes of HPV are genitalto-genital contact and hand-to-genital contact. Although rare, transmission through breastfeeding and vertical transmission through the placenta in pregnant female have also been reported [17][18][19].…”
Section: Human Papillomavirusmentioning
confidence: 99%
“…However, other transmission routes are also known [18]. Studies have demonstrated the vertical transmission of HPV from mother to fetus, as well as the presence of HPV viral DNA in breast milk, amniotic fluid, the umbilical cord, and the placenta [19][20][21]. Newborns can also become infected through skin-to-skin contact with other relatives, as well as oral lesions related to HPV infection, such as oral squamous papilloma, condyloma acuminatum, verruca vulgaris, and multifocal epithelial hyperplasia; genital HPV infection in children is a warning sign for sexual abuse [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%